METHODICAL BASES OF EDUCATIONAL INFORMATION ENVIRONMENT FORMATION IN THE TECHNICAL HIGHER EDUCATIONAL INSTITUTIONS - Рахманов, В. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article considers methodological principles of educational information environment formation of higher technical education. It will provide the necessary conditions to improve the educational process, to deepen professional knowledge of the students and tutors’ competence. Creation of information, software and didactic support system technical higher educational institution, adaptation of software and computer systems to the terms of the educational process, validation of methods of their use is a relevant theoretical and methodological problem that is going to have an important scientific and educational value. The article analyzes the feedback technology as a comparative process of the knowledge level and established educational standards. Feedback is also seen as a reaction to the knowledge that helps students to identify whether the information was perceived or not by him. It will allow the tutor to determine the level of students’ knowledge more accurately, this knowledge would have a further positive impact on studying process